KEANEKARAGAMAN BIOTA PERAIRAN SUNGAI (PLANKTON) DI LAPANGAN GAS SENORO KABUPATEN BANGGAI, SULAWESI TENGAH - Tis'in, Musayyadah (AgriSains, 2017)
The research aim to evaluated compotition, density, and diversity of plankton at 2016 years in the development site of Senoro gas field. The Method that has been used is deskriptif survey and purpose sampling and set 9 stasiun in 9 rivers. The result of the reseach show that phytoplankton diversity was highest in Kayowa River (very good category) and lowest in Uso river (good category). While zooplankton diversity was highes in Mading river (2,75) and lower in Paisubuloli river (1,95). The conclusion of the reseach are the development sites of Senoro Gas Field have high diversity and steady community.Keyword: Coral reefs, production flare, tiaka oil field